Avaliação da eficácia da gestão de pesquisa nos Parques Estaduais de São Paulo - Pegler, Gabriela Francisco (2018)
Protected areas are considered one of the most important elements for biodiversity conservation. One of the pillars that sustain the management of these areas is scientific research, which provides the knowledge necessary for the conservation of environmental and historical-cultural heritage. The general objective of the present study was to evaluate the current state and propose improvements in the management of research of the State Parks of São Paulo in light of already existing practices of Knowledge Management. By the analysis of Research Programs present in the Management Plans of the Units, we identify the main aspects that underpin the research management and evaluate their effectiveness within the current context of each Park and for all the system (set of Parks). The main challenges pointed out in the evaluation were related to the lack of assurance regarding the return of the results of the surveys for management of the areas; the insufficiency of human resources directed to the execution of the activities foreseen in the Research Programs and the monitoring process carried out without periodicity and systematization. We could also observe the low correlation between well-managed Management Plans and Research Programs and the satisfactory performance of the actions foreseen in these documents, suggesting that the process of research management in these areas is not necessarily being directed by some planning instrument.